Formulation and quality evaluation of Multigrain Neutra-chikki (International Journal of Food and Nutritional Sciences, 2022)
An organism assimilates food and utilises it for development and maintenance through the process of nutrition, which is an organic process of nourishing or being fed. The study of food and drink in humans is a field of science that provides sources of nutrients for the body. Nutrition is the process of giving the materials required for life in the form of food to cells and organisms. A healthy diet can prevent or treat a number of common health issues.Chikki a traditional candy delicacy created with groundnut and jaggery is enjoyed by people of all age group in India. An attempt was made to improve its nutritional quality by developing a multigrain Nutra-chikki with pumpkin seed, fennel seed and peanut, and the nutritional assessment were evaluated. The prepared multigrain Nutra-chikki was also organoleptically assessed using a sensory affective hedonic scale.The results indicates that multigrain Nutra-chikki comprises of protein 14.78 g, fat 16.6 g, and minerals like iron 9.67 mg, calcium 269.9 mg which is nutritionally superior to groundnut chikki. It also showed acceptable sensory score of 8.3 for overall characteristics against groundnut chikki.